What are the fiscal limits for the developing economies of Central America and the Caribbean? - Francisco A. Ramirez; Allan Wright (Inter-American Development Bank (IDB), 2017)
This study uses simulations of state-dependent distributions of fiscal limits for 18 economies in Central America and the Caribbean to better understand governments' ability to service their debt, arising from endogenously determined dynamic Laffer curves. Using a small, open economy model to simulate macroeconomic fundamentals and fiscal policy interactions, the empirical findings produced results not previous available for these economies, showing varying and wider distributions of fiscal limits for the open economy model subject to terms-of-trade and flexible exchange rate shocks. This indicates that terms-of-trade and exchange rate volatility impacted the ability of national economies to service their debt. It is therefore prudent that policymakers and central bankers consider models that incorporate the use of trade and exchange rate volatility as a robust way of more accurately determining fiscal limits, which are a critical component in understanding governments' ability to service their debt.
hdl:11319/8269
Keywords: C15; E62; H60; O54; 330; fiscal limits; Laffer curves; debt and developing economies